THE CAPITAL FORMATION AS THE FORMATION OF THE PROPERTY OF EMPLOYEES IN THE DEVELOPMENT OF MODERN MARKET ECONOMY - Bash, O. S. (Science and Transport Progress, 2006)
The article considers issues of formation of hired employees’ joint-stock property in the conditions of presentday market economy in Ukraine.